MENGUJI KOMPLEKSITAS ILLAH HADIS - Hairul Hudaya (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2012)
One step of the verification of the validity of the hadith is to test the aspect of illahwhether in sanad, content or the combination of both. Illah is understood as a form ofhidden defects in the hadith. It distinguishes between muallal hadith and other weakhadith. The hadith scholars acknowledge that the research of Illah aspect is one of themost difficult to test the validity of the hadith. To determine the complexity of illahstudies, it is needed to review of the content and the chain of transmission of hadithwhich contained an illah by the hadith scholars. The result proved that the proof ofillah of a hadith was not easy. Hadith is born valid but apparently assessed withillah.